PENGARUH PERMAINAN SPACE OUTBOUND TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TK PERMATA KASIH BUNDA KTJ KABUPATEN INDRAGIRI HILIR - Desti Eka Yuliana; Zulkifli N Zulkifli N; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: In this study there are problems regarding the gross motor development of children who have not been stimulated such as (balance, mimicking motion, playing by rules, distinguishing right and left, washing hands after playing). This study aims to find out the influence of space outbound games on the gross motor skills of children aged 5-6 years. This research is quantitative research with a type of experimental research with the design of one group pre-test post-test design. The population and sample of this study were 5-6 years old children, numbering 15 children. Observation data collection techniques and data analysis techniques use t-tests using the Windows ver.25 SPSS program. The test is used as a data collection technique, the data obtained is then processed using the t-test to see the comparison of pretest and posttest. Based on the analysis of data known thitung = 24,180 >ttabel = 1.76131 with Sig. (2-tailed) = 0.000 because Sig< 0.05. This means that there is an influence of space outbound games on the gross motor skills of children aged 5-6 years which is significant at 42.33%.Key Words: Space Outbound Games, Gross Motor Skills